EFFECT OF HEAT TREATMENT ON THE RHEOLOGICAL PROPERTIES AND COLOR OF PUMPKINS (Cucurbita moschate) - Silva, Keila de Souza; Garcia, Carolina Castilho; Romero, Javier Telis; Mauro, Maria Aparecida (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2015)
B.CEPPA, Curitiba, v. 33, n. 1, p. 87-97, jan./jun. 2015 EFFECT OF HEAT TREATMENT ON THE RHEOLOGICAL PROPERTIES AND COLOR OF PUMPKINS (Cucurbita moschate) Keila de Souza Silva* Carolina Castilho Garcia** Javier Telis Romero*** Maria Aparecida Mauro**** The aim is to investigate the eff ects of stepwise blanching and its combination with drying on rheological properties and change of color in pumpkins (Cucurbita moschata). 1 cm thick samples were immersed in water at 55 °C for diff erent times, followed by diff erent holding times prior to inactivation of the enzyme (97 °C/5minutes). Controled samples were obtained after blanching at 97 °C for 5 minutes. The texture and color of the samples were measured and the rheological parameters calculated according to the Maxwell model. The results showed that stepwise blanching for 40 minutes with 30 minutes of holding time provided samples with equilibrium modulus of elasticity greater than the control samples. These parameters were used as blanching pre-treatment to convective drying with air at 60 °C and a velocity of 1.5 m/s for diff erent drying times. Stepwise blanched samples showed fi rmer tissues than control samples after drying. There were no signifi cant diff erences in the lightness and redness of stepwise blanched samples and control samples during drying.